What does the EU-SADC EPA really say? An analysis of the economic partnership agreement between the European Union and Southern Africa. Issue 4 (1st October 2016) - Berends, Gijs
ABSTRACT: After more than 10 years of negotiations, the European Union and six members of the Southern Africa Development Community (SADC) successfully concluded talks on an economic partnership agreement (EPA). The EPA is a reciprocal trade agreement under the umbrella of the Cotonou Agreement, under which all parties commit to trade liberalisation but under which the SADC EPA countries can exempt sensitive products from liberalisation so as to take account of their level of development. This article explains in detail the contents of the agreement, examines the degree of trade liberalisation, and explores the lesser known provisions of the EPA. The article then argues that part of the agreement's developmental character resides in the numerous provisions that offer benefits to SADC EPA states but not to the EU. It also highlights provisions that could be invoked to help African states in the process of economic diversification. Finally, contrary to some detractors, the article takes the view that policy space for policy-makers remains by and large respected.